Numerical Modelling of a Cutting Arc Torch - Mancinelli, Beatriz (2014)
Plasma cutting is a process of metal cutting at atmospheric pressure by an arc plasma jet, where a transferred arc is generated between a cathode and a work-piece (the metal to be cut) acting as the anode . Small nozzle bore, extremely high enthalpy and operation at relatively low arc current (≈ 10 ÷ 200) A are a few of the primary features of these torches. The physics involved in such arcs is very complicated. The conversion of electric energy into heat within small volumes causes high temperatures and steep gradients. Dissociation, ionization, large heat transfer rates (including losses by radiation), fluid turbulence and electromagnetic phenomena are involved. In addition, wide variations of physical properties, such as density, thermal conductivity, electric conductivity and viscosity have to be taken into account.